2014
DOI: 10.1002/pssr.201409210
|View full text |Cite
|
Sign up to set email alerts
|

Artificially controlled synthesis of graphene intramolecular heterojunctions for phonon engineering

Abstract: Because phonons are the main carriers for graphene heat transfer, modifying the dynamic properties of the crystal lattice by isotopes modulates the phonon behavior and alters the thermal properties. Here we demonstrate an artificially controlled texture synthesis of 12C‐graphene/13C‐graphene heterostructures via chemical vapor deposition and an O2 plasma etching. The electrical and thermal properties of the graphene across the heterojunction show that 12C‐graphene and 13C‐ graphene are electronically connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Graphene samples with or without isotope heterojunctions were synthesized by low‐pressure thermal CVD using 12 CH 4 and 13 CH 4 as carbon sources. Details of the fabrication procedure for the heterojunctions are described elsewhere . Before transferring graphene onto SiO 2 (500 nm)/Si substrates, Pt electrodes and a microfabricated heater were deposited on the substrate by electron beam evaporation and a liftoff technique.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Graphene samples with or without isotope heterojunctions were synthesized by low‐pressure thermal CVD using 12 CH 4 and 13 CH 4 as carbon sources. Details of the fabrication procedure for the heterojunctions are described elsewhere . Before transferring graphene onto SiO 2 (500 nm)/Si substrates, Pt electrodes and a microfabricated heater were deposited on the substrate by electron beam evaporation and a liftoff technique.…”
Section: Resultssupporting
confidence: 93%
“…Consequently, isotopically modified graphene heterostructures have a great potential to reduce the thermal conductivity. Using the local thermal conductivity at the heterojunction estimated in our previous report (≈200 W m −1 K −1 ), the calculated figure of merit of graphene with heterojunctions is ≈0.008 at room temperature, which is almost ten times higher than that of graphene composed of only 12 C. Although this value does not satisfy the value ZT > 1 for practical applications, it is a significant improvement because both a higher electrical conductivity and a higher thermoelectric power are possible using graphene with larger domains by optimizing the CVD growth conditions and removing impurities in the graphene channels. In addition, graphene samples grown by CVD contain structural defects including 5–8 defects that may increase the electrical conductivity and decrease the thermal conductivity, also improving the thermoelectric performance of graphene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas syntheses of single456789 (SWCNT) and double101112 (DWCNT) walled 13 C isotope carbon nanotubes, quantum dots13 and two dimensional 13 C nanomorphologies such as graphenes have been reported14151617, studies of 13 C multiwalled carbon nanofibers have not been evident, presumably due to the complexity and expense of conventional electrospinning/carbonization or chemical vapor deposition syntheses which would require additional synthetic steps to form the requisite 13 C polymers or 13 C organometallic reactants. Similarly, density functional and molecular dynamic simulation studies are found on 13 C isotope SWCNTs1819, but not on nano-morphologies which would require modeling of a larger numbers of carbon centers.…”
mentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) was performed using Mg-Kα radiation (1253.6 eV), where the binding energy was corrected using the C1s peak at 284.6 eV. After the Au-electrode oxidation, a monolayer graphene was transferred onto the substrate and was trimmed using oxygen plasma etching to form an FET channel (width × length: 5 × 2 and 2 × 4 μm), where the graphene was synthesized using low-pressure chemical vapor deposition at 1000 °C using Cu foil as catalyst 27 28 (see Fig. S1 for Raman spectrum of grown graphene).…”
mentioning
confidence: 99%